Application of the bees algorithm for constrained mechanical design optimisation problem - Kamaruddin, Shafie; Abd Latif, Mohd Arif Hafizi (Deer Hill Publications, 2019)
Optimisation is a technique or procedure to find the optimal or feasible solution whether it is to minimise or maximise by comparing other possible solutions until the best solution is found. Nowadays, many optimisation algorithms have been introduced due to the advancement of technology such as Teaching Learning Based Optimisation (TLBO), Ant Colony Optimisation (ACO), Particle Swarm Optimisation (PSO) and the Bees Algorithm. The Bees Algorithm is considered as one of the best optimisation algorithms because it has been successfully solved different type optimisation problem from in various field. It is inspired by the foraging behaviour of honey bees in nature. This study applies the Bees Algorithm to minimise the mass of disc clutch brake in its design. To find the optimal solution for the multiple disc clutch design, the Bees Algorithm will be used and expected to give better result compared to other optimisation algorithms that already have been used.